Pemendekkan Gairaigo dalam J Bridge for Beginners Vol 1 dan 2 - Putri, Meira Anggia (Journal of Japanese Language Education and Linguistics, 2019)
Japanese loan words are ubiquitous in Japanese lexicon and the using of them are omnipresent in Japanese society. Loan words called gairaigo in Japanese. Gairaigo came from foreign languages (other than Chinese) which are borrowed to Japanese and adapted to Japanese phonological system. The adaptation to Japanese phonological system makes gairaigo longer than the original words, hence to make them easier to be used, gairaigo tend to be shortened. This study discusses about shortening process of gairaigo. Engman (2018) stated that shortening process of gairaigo can be happen in single word (single word truncation) and compound words (compound truncation). Single word truncation known as clipping. Irwin (2016) wrote that clipping consist of back clipping, fore clipping and mid clipping, and compound truncation consist of morpho-ortographic truncation, compound clipping, and ellipsis. Data source of this study are J Bridge for beginners volume 1 and 2. The type of research is qualitative research with descriptive method. Loan words, gairaigo, clipping, truncation, ellipsis